Action of Multiple Rice β-Glucosidases on Abscisic Acid Glucose Ester - Kongdin, Manatchanok (Int J Mol Sci, 2021)
Conjugation of phytohormones with glucose is a means of modulating their activities, which can be rapidly reversed by the action of β-glucosidases. Evaluation of previously characterized recombinant rice β-glucosidases found that nearly all could hydrolyze abscisic acid glucose ester (ABA-GE). Os4BGlu12 and Os4BGlu13, which are known to act on other phytohormones, had the highest activity. We expressed Os4BGlu12, Os4BGlu13 and other members of a highly similar rice chromosome 4 gene cluster (Os4BGlu9, Os4BGlu10 and Os4BGlu11) in transgenic Arabidopsis. Extracts of transgenic lines expressing each of the five genes had higher β-glucosidase activities on ABA-GE and gibberellin A(4) glucose ester (GA(4)-GE). The β-glucosidase expression lines exhibited longer root and shoot lengths than control plants in response to salt and drought stress. Fusions of each of these proteins with green fluorescent protein localized near the plasma membrane and in the apoplast in tobacco leaf epithelial cells. The action of these extracellular β-glucosidases on multiple phytohormones suggests they may modulate the interactions between these phytohormones.